2005
DOI: 10.1590/s0073-47212005000200002
|View full text |Cite
|
Sign up to set email alerts
|

Distribuição de peixes na microbacia do Ribeirão Grande, Serra da Mantiqueira Oriental, São Paulo, Brasil

Abstract: ABSTRACT. Fish distribution in the Ribeirão (April 2002). Conductivity, pH, water temperature and dissolved oxygen were measured for each site, and elevations in meters were taken by a GPS receiver. The spatial dimension was the main source of variability in the fish distribution in the Ribeirão Grande system. A total of 37 species were caught and the ten most abundant species correspond almost 90% of the total catch. Pareiorhina rudolphi was caught principally in the slope; Characidium lauroi, Trichomycterus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
16

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 12 publications
1
25
0
16
Order By: Relevance
“…Ribeirão Grande and other neighboring systems form a left-side Paraíba do Sul drainage basin (Figure 1 Collections were made with an electro-fishing device, powered by a generator with maximum capacity of 1,500 V and 8.7 of 60 Hz alternating current. All specimens were preserved in 10% formalin and returned to the laboratory for identification and biometryc (Braga, 2004;Braga and Andrade, 2005). In the laboratory, the stomachs were rinsed in tape water and preserved in 70% alcohol.…”
Section: Study Area Study Area Study Area Study Areamentioning
confidence: 99%
See 3 more Smart Citations
“…Ribeirão Grande and other neighboring systems form a left-side Paraíba do Sul drainage basin (Figure 1 Collections were made with an electro-fishing device, powered by a generator with maximum capacity of 1,500 V and 8.7 of 60 Hz alternating current. All specimens were preserved in 10% formalin and returned to the laboratory for identification and biometryc (Braga, 2004;Braga and Andrade, 2005). In the laboratory, the stomachs were rinsed in tape water and preserved in 70% alcohol.…”
Section: Study Area Study Area Study Area Study Areamentioning
confidence: 99%
“…Analyses of variance homogeneity were carried out to test the null hypothesis of no differences between females and males of both species. After, slopes (B) were tested for homogeneity; then, if this criterion was satisfied, the elevation (A) tested, using P=0.05 (Fowler et al, 1998). When the variances were different (P<0.05) a test that analyzed only slopes was carried out.…”
Section: Study Area Study Area Study Area Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…Spatial patterns of species distribution have been addressed in several studies (Uieda, 1984;Garutti, 1988;Uieda and Barreto, 1999;Silvano et al, 2000;Mazzoni and Lobón-Cerviá, 2000;Uieda and Uieda, 2001;Pavanelli and Caramaschi, 2003;Castro et al, 2003;Súarez and Petrere, 2003;Súarez and Petrere, 2005;Castro et al, 2004;Casatti, 2005;Braga and Andrade, 2005;Cetra and Petrere, 2006) that, in general, reported an increase in species diversity since the headwaters to the mouth in fish communities at different locations. The relationship between habitat and community composition was presented by Montag et al (1997), Benedito-Cecilio et al (2004) and Gomiero and Braga (2006), which showed the correlations between habitat diversity and general conditions in the environment.…”
Section: Introductionmentioning
confidence: 99%